Effect of Crop Load on the Quality of Cabernet Sauvignon Grapes and Wines at Different Harvest Times - GE Qian, ZHANG Yuanke, YAN Yue, KAI Jianrong, ZHOU Xinming, JIANG Wenguang, LI Xinghong, CHANG Tengwen, YI Zicheng, SUN Xiangyu, ZHANG Zhenwen, LI Jiming (Shipin Kexue)
In this study, three levels of grape load (15, 20, and 25 spikes/m shelf) were set for the primary wine grape cultivar ‘Cabernet Sauvignon’. The effect of different harvest times, four growth stages according to the Eichhorn-Lorenz scale: E-L35, E-L36, E-L37, and E-L38 was investigated on the compositions of organic acids, monomeric phenols and volatile compounds and sensory quality of wine. The results showed that at the E-L38 stage, the total acid of grape berries in the medium-load group significantly increased, while the opposite was true for the low- and high-load groups. For all groups, the total acid content of wine peaked at the E-L35 stage and reached its lowest point at the E-L37 stage. The total phenol content reached its peak at the E-L36 stage, and then decreased rapidly. Under the low-load condition, the sensory quality of wine produced from early harvested grapes was superior to that of late harvested grapes, whereas the opposite result was found at the high load. The typicality and richness of wine were significantly improved with the delay of harvest time, samples J-20-6 (medium load + E-L37) and J-20-7 (medium load + E-L38) outperforming all other samples. The overall sensory score of sample J-20-5 (medium load + E-L36) was the highest, and the total volatile content and sensory richness score of sample J-25-7 (high load + E-L38) were the highest among all tested samples. Thus, meticulous regulation of grape load and harvest time holds substantial promise for enhancing wine quality.